Implementation of kurikulum merdeka for Muhammadiyah pandes primary students Special Region of Yogyakarta - Muhammad Dzulqarnain Izzuddien Abdul Ahad; Hendro Widodo (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Enhancing Indonesian education standards is the goal of Kurikulum Merdeka. This research was motivated by the Independent Class Strategy of the Indonesian Ministry of Education and Culture. This study aims to give a summary of Muhammadiyah Pandes Elementary School in Yogyakarta's Special Region's implementation of the Independent Curriculum. In order to ascertain the general condition of the exploration item, this investigation employs qualitative descriptive approaches. Academic stars were the main exploration subjects for the research, and validation, interviews, and observation collected data. The Kurikulum Merdeka component of SD Muhammadiyah Pandes Elementary School's research encompasses student characteristics, infrastructure and facilities, socio-cultural elements, partnerships established by the school, and the features of the educational unit made up of masters and supporting staff. The school has a four-year plan outlining its vision, aims, and objectives. First, diagnose and assess, then make necessary revisions to the plan, execute assessments and the primary learning activities, and lastly, assess and evaluate the entire learning process. Two parts comprise the operational analysis process of the curriculum in the learning unit: recording learning objectives and outcomes, processing assessment findings, providing support for professional development and evaluation activities, and encouraging self- and peer-reflection. AbstrakMeningkatkan standar pendidikan Indonesia adalah tujuan Kurikulum Merdeka. Penelitian ini dimotivasi oleh Strategi Kelas Mandiri Kementerian Pendidikan dan Kebudayaan RI. Penelitian ini bertujuan untuk memberikan ringkasan implementasi Kurikulum Merdeka di SD Muhammadiyah Pandes Daerah Istimewa Yogyakarta. Untuk mengetahui kondisi umum barang eksplorasi, penelitian ini menggunakan pendekatan deskriptif kualitatif. Bintang akademis menjadi subjek eksplorasi utama penelitian ini, dan data dikumpulkan melalui validasi, wawancara, dan observasi. Komponen Kurikulum Mandiri SD Muhammadiyah Pandes yang diteliti meliputi karakteristik peserta didik, prasarana dan sarana, unsur sosial budaya, kemitraan yang terjalin oleh sekolah, dan ciri satuan pendidikan yang terdiri dari magister dan tenaga penunjang. Sekolah memiliki rencana empat tahun yang menguraikan visi, sasaran, dan sasarannya. Pertama, mendiagnosis dan menilai, kemudian melakukan revisi yang diperlukan terhadap rencana, melaksanakan penilaian dan kegiatan pembelajaran utama, dan terakhir, menilai dan mengevaluasi seluruh proses pembelajaran. Ada dua bagian yang membentuk proses analisis operasional kurikulum di unit pembelajaran: mencatat tujuan dan hasil pembelajaran, memproses temuan penilaian, memberikan dukungan untuk pengembangan profesional dan kegiatan evaluasi, dan mendorong refleksi diri dan rekan sejawat.Kata Kunci: sekolah dasar; implementasi; kurikulum merdeka